The INNOVO multicentre randomised controlled trial: neonatal ventilation with inhaled nitric oxide versus ventilatory support without nitric oxide for severe respiratory failure in preterm infants: follow up at 4–5 years. Issue 6 (28th March 2008) - Huddy, C L; Bennett, C C; Hardy, P; Field, D; Elbourne, D; Grieve, R; Truesdale, A; Diallo, K; ,
Abstract : Background: Trials of inhaled nitric oxide (iNO) used short term in preterm infants with severe respiratory failure have to date shown no evidence of benefit, and there have been no trials reporting follow-up to 4 years of age. The INNOVO trial recruited 108 infants (55 iNO arm and 53 controls) from 15 neonatal units. By 1 year of age 59% had died, and 84% of the survivors had signs of impairment or disability. Objective: This paper reports the long-term clinical effectiveness and costs of adding NO to the ventilator gases of preterm infants with severe respiratory failure. Patients and methods: Children were assessed at age 4–5 years by interview, examination, cognitive and behavioural assessments. The outcome data were divided into seven domains and were described as normal, impaired or disabled (mild, moderate or severe) by the degree of functional loss. Results: 38 of the 43 survivors had follow-up assessments. In the iNO group 62% (34/55) had died or were severely disabled, compared to 70% (37/53) in the no iNO group (RR 0.89, 95% CI 0.67 to 1.16). There was no evidence of difference in the levels of impairment or disability between the two groups in any of the domains studied, or of cost differences, amongst the survivors. Conclusion: For this group of babies with severe respiratory failure there was no evidence of difference in the longer-term outcome between those babies allocated to iNO and those who were allocated to no iNO. The challenge is to identify those premature babies who are able to respond to NO with clinically important health improvements. Trial registration number: 17821339.